(untitled) (Bangladesh Journal of Agriculture, 2022)
Radio and television are the most influential mass media to stimulate farming community to proper direction of their farming works. These two powerful media have proved to be most useful ICT tools in the field of agricultural information source. Different studies reveal that farmers obtained right and time bound information from radio and television channels. This study was carried out to assess the role of radio and television in the dissemination of agricultural technologies among farmers in some regions of Bangladesh. It was conducted to assess how radio and television are contributing to the growth of agriculture sector. The study also reveals some problems faced by the farmers in using radio and television. A random sampling technique was used on 1170 respondents to collect the data through a well structure questionnaire. The study results point out that the radio and television had an effective role in improving awareness and increasing the modern technological knowledge of farmers. The television and radio programs also helped farmers’ access marketing information. The study showed that the respondents have different degree of accessibility to different radio and television channels on agricultural programs. Bangladesh J. Agri. 2019-2021, 44-46: 55-64